Perbedaan asupan energi, zat gizi makro dan mikro pada mahasiswa S2 IKM reguler yang stress - Ice Yolanda Puri; Pernodjo Dahlan; Ita Paramastri (Jurnal Gizi Klinik Indonesia, 2006)
Background: In general, sufferers of stress lose appetite, although sometimes some of them eat more than usual. If they lose appetite, there will be energy and protein deficiency. This condition will disrupt antibody so that they can get easily infected. Stress causes nutrition absorption disorder and then reduces antibody. Emotional and environmental stress will lose vitamin C as much as 2500 mg within a short period. Another bad impact is reducing supply of vitamin B12, vitamin C, calcium and zinc.Objective: To identify differences of energy, macronutrient (carbohydrate, protein, and fat) and micronutrient (vitamin C, vitamin B12, calcium and zinc) intake among postgraduate students of public health sciences (Health Policy Management and Service, Health Nutrition and Mother and Child Health Reproduction) with low, middle and high stress.Method: The study was an observational type which used a nested case control design. It used a quantitative approach to analyze stress and intake of energy, macronutrient (carbohydrate, protein and fat) and micronutrient (vitamin C, B12, calcium and zinc). Subject of the study were as many as 34 postgraduate students of public health sciences of Gadjah Mada University of academic year 2004/2005. Data of respondents’ identity, intake of protein, macronutrient and micronutrient and stress were achieved directly through questionnaires. Intake data were taken from food record form with multiple record 4 x 24 methods which were collected for a month to represent all days. Anthropometric data used was body weight. Data of stress were collected using stress questionnaires. Intake data analysis used NutriSurvey program. Anova test were used to identify differences of aver-age consumption of macro and micro nutrients.Result: There was no difference of macronutrient and micro-nutrient intake with low, middle and high stress. Result of Anova analysis showed that there was no significant difference be-tween intake of macronutrient and micronutrient and level of stress.Conclusion: There was no significant difference of macronutrient and micronutrient intake with low, middle and high level of stress among postgraduate students of public health sciences of academic year 2004/2005.